Rhetoric Matters A Guide to Success in the First Year Writing Class - Falik, Adam; La Rue, Dorie; Watts, Tracey (Open textbook library., 2021)
Rhetoric Matters: A Guide to Success in the First Year Writing Class offers students necessary concepts and practice to learn all the elements needed for successful first year writing and set the stage for future writing success in college. This textbook was created as part of the Interactive OER for Dual Enrollment project, facilitated by LOUIS: The Louisiana Library Network and funded by a $2 million Open Textbooks Pilot Program grant from the Department of Education. This project supports the extension of access to high-quality post-secondary opportunities to high school students across Louisiana and beyond. This project features a collaboration between educational systems in Louisiana, the library community, Pressbooks technology partner, and workforce representatives. It will enable and enhance the delivery of open educational resources (OER) and interactive quiz and assessment elements for priority dual enrollment courses in Louisiana and nationally. Developed OER course materials will be released under a license that permits their free use, reuse, modification and sharing with others.The target audience for this project and this textbook are dual enrollment students. Dual enrollment is the opportunity for a student to be enrolled in high school and college at the same time. A dual enrollment student receives credit on both their high school and college transcripts for the same course.